On the properties of an operator of stochastic differentiation constructed on a group - Pilipenko, A. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We construct a differential operator by an admissible group in the space L 2 (ℝm,P)and study its properties.